Why Do Parents with Toddlers Store Poisonous Products Safely? - Tinneke M. J. Beirens; Eduard F. van Beeck; Johannes Brug; Paul den Hertog; Hein Raat (Hindawi Limited, 2010)
Unintentional poisoning is a major cause of nonfatal injuries in children aged 0-24 months. Associations between self-reported habits on the child safe storage of medication and cleaning products and family, and psychosocial factors were assessed, using a model based on the Protection Motivation Theory. By identifying correlates of safety behavior in this manner, more insight in factors which influence this behavior is obtained. Health promotion activities in order to promote safety behavior should address these factors in order to increase the effectiveness of the health message. Data were gathered from a cross-sectional survey using self-administered questionnaires, mailed to a population sample of 2470 parents with toddlers. The results indicate that the promotion of safe storage of medication and cleaning products should address the family situation, personal cognitive factors as well as social factors. Interventions should particularly focus on parents' self-efficacy of storing poisonous products in a child safe manner and on the vulnerability of their child in their home concerning an unintentional poisoning incident.